2006
DOI: 10.1111/j.1463-6409.2006.00224.x
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary revision of the genusPlecotus(Chiroptera, Vespertilionidae) based on genetic and morphological results

Abstract: Haring, E. (2006). A preliminary revision of the genus Plecotus (Chiroptera, Vespertilionidae) based on genetic and morphological results.-Zoologica Scripta , 35 , 187-230. The phylogenetic relationships within the genus Plecotus were assessed using molecular as well as morphological methods. With only three species missing, our study is based on an almost comprehensive taxonomic sampling. The genetic analysis comprised 151 individuals from throughout the range. Sequences of two mitochondrial sections, parts o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
129
0
7

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(141 citation statements)
references
References 34 publications
(105 reference statements)
5
129
0
7
Order By: Relevance
“…-Tinnin et al 2002;Simmons 2005 Literature. -Desportes 1946;Biocca and chabaud 1951;Spassky, Ryjhikov and Sudarikov 1952;coil and Kuntz 1958;Soltys 1959;andreiko and Skvortsov 1968;Zdzitowiecki 1969;Skvortsov 1970;Zdzitowoecki 1970a;Tokobaev 1976;Sawada 1980;Khotenovskii 1985;Sawada 1990;Tkach et al 2000;Shimalov et al 2002;Tinnin et al 2002;Spitzberger et al 2006;Dolch et al 2007;Tinnin et al 2008;Batsaikhan et al 2010.…”
Section: Hypsugo Alashanicus Bobrinskii 1926 Alashan Batmentioning
confidence: 99%
See 1 more Smart Citation
“…-Tinnin et al 2002;Simmons 2005 Literature. -Desportes 1946;Biocca and chabaud 1951;Spassky, Ryjhikov and Sudarikov 1952;coil and Kuntz 1958;Soltys 1959;andreiko and Skvortsov 1968;Zdzitowiecki 1969;Skvortsov 1970;Zdzitowoecki 1970a;Tokobaev 1976;Sawada 1980;Khotenovskii 1985;Sawada 1990;Tkach et al 2000;Shimalov et al 2002;Tinnin et al 2002;Spitzberger et al 2006;Dolch et al 2007;Tinnin et al 2008;Batsaikhan et al 2010.…”
Section: Hypsugo Alashanicus Bobrinskii 1926 Alashan Batmentioning
confidence: 99%
“…In Mongolia they are known from the southern Khangay and Mongolian altai across the south of the country. Comments.-Similarly to P. auritus, Spitzberger et al (2006) Literature. -Yanchev and Stoikova 1973;Murai 1976;Shimalov et al 2002;Tinnin et al 2002;Simmons 2005;Spitzberger et al 2006;Dolch et al 2007;Batsaikhan et al 2010.…”
Section: Plecotus Austriacus (Fischer 1899)mentioning
confidence: 99%
“…The members of the genus Plecotus (long-eared bats) are widely distributed in the Palearctic (Spitzenberger et al, 2006), and six European species have been confirmed to date. Phylogenetic analyses revealed the existence of two major lineages of long-eared bats in Europe: the 'auritus group' (P. auritus, P macrobullaris, and P. sardus), and the 'austriacus group' (P. austriacus, P. kolombatovici, and P. teneriffae) (Mucedda et al, 2003;Juste et al, 2004).…”
mentioning
confidence: 99%
“…It is present in the Pyrenees (Garin et al, 2003;Alberdi et al, 2013), the Alpine ridge Spitzenberger et al, 2002;Trizio et al, 2005;Presetnik et al, 2009), the Dinarides (Pavlinić and Tvrtković, 2004;Tvrtković et al, 2005;Sachanowicz and Ciechanowski, 2006;Karapandža et al, 2014;Presetnik et al, 2014), the Pindos Mountains , Crete (Juste et al, 2004), Anatolia (Karataş and Sözen, 2006), and mountainous regions in the Middle East and the Caucasus (Benda et al, 2006;Spitzenberger et al, 2006;Kiefer, 2008), showing an alpine distribution pattern and being the most common bat species in the alpine area in Europe (Alberdi et al, 2013).…”
mentioning
confidence: 99%
See 1 more Smart Citation